'Barahunga Amahoro—They Are Fleeing Peace!' The Politics of Re-Displacement and Entrenchment in Post-War Burundi. (23rd August 2016) - Purdeková, Andrea
Abstract : Ahead of the 2015 contested elections, Burundi got embroiled in a vast refugee crisis only a decade after the end of the civil war. Against the official government efforts to depoliticize the crisis, the article draws on interviews with Burundians across space and time to underscore the fundamentally political character of migration decisions after the war, and argues for the applicability of the social contract theory for a bottom-up conception of political incorporation and citizenship. The evidence suggests that the current wave is no 'repeat', but rather that people are entrenching in displacement against the negative trust capital incurred by the state. People's narratives complicate the very terms of displacement by offering an alternative conception of belonging—through transtemporal and transnational comparisons, they see their movements as amongst a set of 'partial citizenship regimes'. More broadly, the article hopes to contribute to our understanding of re-displacement and entrenchment (as the refusal to move) and, more broadly, people's politico-spatial orientations in post-war space as well as the subversions of this order from below through strategies both physical and discursive.